Efficiency in the Performance of Professional Accountants According to the Code of Ethics for Professional Accountants - Sangkatat, Sunanta (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The code of ethics of professional accountants according to the Federation of Accounting Professions’ regulations on the ethics of professional accountants B.E. 2018 which consists of 1) honesty 2) fairness and independence, 3) competent and attentiveness and maintaining standards in operations, 4) confidentiality 5) professional behavior and 6) transparency, all affected the efficiency in the professional accountants performance. It emphasized on ethical conduct in the profession for professional accountants to use as a guideline for performing their duties correctly, encouraged professional accountants to develop themselves to be good people with morality, developed work in duties and organizations for efficiency and effectiveness. It also developed accounting professional work to advance and keep pace with changes in today’s digital age.